PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL DISCOVERY LEARNING PADA MATERI TRANSFORMASI GEOMETRI KELAS XI MA/SMA - Amir Muhammad Hidayatullah; Wisnu Siwi Satiti; Chusnul Chotimah (JoEMS (Journal of Education and Management Studies), 2020)
This research is aimed to measure the effectivity of Problem Based Learning Models andit’s application to the learning process. The subject of this research is the student of XI MIPA II Madrasah Aliyah Unggulan KH.Abd.Wahab Hasbullah Jombang that contains 19 students. Meanwhile, the object of this research is mathematics learning process using Discovery Learning. This research was done using the experimental method. The application of Scientific is giving a treatment to the subject of the research, and observe the results of the experiment. The result of this research shown that the application of Discovery learning models can make the classical completeness of the class reaching.